2016
DOI: 10.1021/acs.langmuir.6b02962
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Drying of Noncircular Sessile Nanofluid Droplets toward Multiscale Surface Patterning Using a Wall-Less Confinement Architecture

Abstract: Surface patterning with functional colloids is an important research area due to its widespread applicability in domains ranging from nano-electronics, pharmaceutics, semi-conductors, photovoltaics among others. To this endeavour, we propose a low-cost patterning technique that aspires to eliminate the more expensive methodologies presently in practise. Using a simple document stamp on which patterns of any geometry can be embossed, we are able to print two-dimensional mm-scale "wall-less confinement" using in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Sessile droplets containing dispersed colloids drying on solid surfaces generate a spectrum of fluid flow patterns such as radial fluid flow, , interfacial flow, and Marangoni flow . The interplay of these flow fields is known to give rise to a plethora of evaporation-driven hierarchical assembly of colloids. These flows and thereby the final deposition pattern could be altered/controlled by controlling the temperature gradients across the drop, ,, fluid evaporation rate, hardness of the substrate, relative humidity, etc. ,, Another way to tailor the flow fields is by the inclusion of additives into the colloidal dispersion like surface active agents and polymers. ,, In addition, the shape of the colloids in the drop can also significantly affect both the radial and interfacial flows . A commonly observed drying drop pattern is a ring-shaped stain formed at the periphery of the drop, known as “coffee rings” and is a result of the dominant radial fluid flow generated in the drop.…”
Section: Introductionmentioning
confidence: 99%
“…Sessile droplets containing dispersed colloids drying on solid surfaces generate a spectrum of fluid flow patterns such as radial fluid flow, , interfacial flow, and Marangoni flow . The interplay of these flow fields is known to give rise to a plethora of evaporation-driven hierarchical assembly of colloids. These flows and thereby the final deposition pattern could be altered/controlled by controlling the temperature gradients across the drop, ,, fluid evaporation rate, hardness of the substrate, relative humidity, etc. ,, Another way to tailor the flow fields is by the inclusion of additives into the colloidal dispersion like surface active agents and polymers. ,, In addition, the shape of the colloids in the drop can also significantly affect both the radial and interfacial flows . A commonly observed drying drop pattern is a ring-shaped stain formed at the periphery of the drop, known as “coffee rings” and is a result of the dominant radial fluid flow generated in the drop.…”
Section: Introductionmentioning
confidence: 99%
“…By reshaping the contact line, the drop shape can be naturally molded to any custom form with multiple curvatures. Although Hancock et al 87 have demonstrated methods for such shape modulation, Kabi et al 88 presented a low-cost and indigenous technique without sophisticated preparations. Fabrication is detailed elsewhere.…”
Section: ■ Chemical Tailoring By Surfactant Additionmentioning
confidence: 99%
“…Fabrication is detailed elsewhere. 88 A cleaned glass slide is treated with plasma for enhanced hydrophilicity; subsequently, hydrophobic lines are stamped onto its surface using an ordinary document stamp to create a wall-less confinement. Since the interior region of the confinement is highly wettable, deployed liquid spreads and completely fills it.…”
Section: ■ Chemical Tailoring By Surfactant Additionmentioning
confidence: 99%
“…Novel and indigenous techniques have demonstrably reduced manufacturing costs. , Additionally, open channels dispense with the need to bond channels, which makes it a one-step fabrication process . Both active and passive methods of actuation discussed in the preceding paragraph can be easily adapted to open channels. Several groups (including the authors) have designed templates of guided wettability which can drive liquid droplets or rivulets without the need for active pumping. One of the most attractive features of a microfluidic device (MFD) is to split, merge, or mix liquid streams using a combination of embedded valves and junctions . However, such designs are not easily reconfigurable and demand a large turnaround time.…”
Section: Introductionmentioning
confidence: 99%
“…Since drop motion is geometry-driven, shape modulation is done by guiding the droplet through a reconfigurable template. 31 For simplicity of demonstration and understanding, a long droplet (initial height h 0 is smaller than contact length l, where h/l ≈ 0.01 and the initial contact angle is ∼10°; see section 2) is created. Actuation is achieved by communication between two droplets via the vapor phase.…”
Section: ■ Introductionmentioning
confidence: 99%